2011
DOI: 10.1007/s00106-011-2346-4
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotaktiles Neurofeedbacktraining mit dem Vertiguard®-RT-System

Abstract: Individualized vibrotactile neurofeedback training as presented here with the Vertiguard® system appeared to improve balance during daily activities in all patient groups investigated, but not in controls. Future studies should investigate the efficacy of this new method in a larger sample as well as its long term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Generally, vibration cues are provided as feedback when body movements exceed a predefined threshold. The effects of VTF applied to the trunk for reducing postural sway in young, healthy subjects, and individuals with vestibular deficits have been validated in several previous studies ( 16 19 ). Moreover, studies have shown that VTF can reduce trunk tilt and improve gait performance in older adults ( 15 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 84%
“…Generally, vibration cues are provided as feedback when body movements exceed a predefined threshold. The effects of VTF applied to the trunk for reducing postural sway in young, healthy subjects, and individuals with vestibular deficits have been validated in several previous studies ( 16 19 ). Moreover, studies have shown that VTF can reduce trunk tilt and improve gait performance in older adults ( 15 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 84%